Developing teachers : the challenges of lifelong learning - Day, Christopher, 1943- (Educational change and development series., 1999)
Effective schools or improving schools are fashionable terms in the rhetoric of recent education movements, yet the heart of these movements is often more to do with teaching quality than with school practice. This book takes a holistic view of teacher development, examining the contexts and conditions of teaching: school leadership and culture; teachers' lives and histories; change; teacher learning, competence and expertise; and the moral purposes of teaching. Day looks at the conditions under which teacher development may be enhanced, and brings together research and other information, from the UK and overseas.